Auxin-Glucose Conjugation Protects the Rice (Oryza sativa L.) Seedlings Against Hydroxyurea-Induced Phytotoxicity by Activating UDP-Glucosyltransferase Enzyme - Kantharaj, Vimalraj; Ramasamy, Nirmal Kumar; Yoon, Young-Eun; Cheong, Mi Sun; Kim, Young-Nam; Lee, Keum-Ah; Kumar, Vikranth; Choe, Hyeonji; Kim, Song Yeob; Chohra, Hadjer; Lee, Yong Bok (Frontiers in Plant Science, 2022)
Hydroxyurea (HU) are the replication stress known to carry out cell cycle arrest by inhibiting ribonucleotide reductase (RNR) enzyme upon generating excess hydrogen peroxide (H2O2) in plants. Phytohormones undergo synergistic and antagonistic interactions with reactive oxygen species (ROS) and redox signaling to protect plants against biotic and abiotic stress. Therefore, in this study, we investigated the protective role of Indole-3-acetic acid (IAA) in mitigating HU-induced toxicity in rice seedlings. The results showed that IAA augmentation improved the seedling's growth and biomass production by maintaining photosynthesis metabolism under HU stress. This was associated with reduced H2O2 and malondialdehyde (MDA) contents and improved antioxidant enzymes [superoxide dismutase (SOD), ascorbate peroxidase (APX), catalase (CAT), and peroxidase (POD)] activity that were significantly affected under HU stress. Further, we showed the HU stress-induced DNA damage leading to activation of uridine 5'-diphosphate-glucosyltransferase (UGT), which mediates auxin homeostasis by catalyzing IAA-glucose conjugation in rice. This IAA-glucose conjugation upregulates the RNR, transcription factor 2 (E2F2,), cyclin-dependent kinase (CDK), and cyclins (CYC) genes that are vital for DNA replication and cell division. As a result of perturbed IAA homeostasis significantly enhanced the key phytohormones such as abscisic acid (ABA), salicylic acid (SA), cytokinin (CTK), and gibberellic acid (GA), that alter plant architecture by improving growth and development. Collectively, our results contribute to a better understanding the physiological and molecular mechanisms underpinning improved growth following the HU+IAA combination, activated by phytohormone and ROS crosstalk upon hormone conjugation via UGT.